Adjusting the lens : community and collaborative video in Mexico - Schiwy, Freya; Wammack Weber, Byrt (Illuminations (Pittsburgh, Pa.), 2017)
"Adjusting the Lens offers a detailed analysis of contemporary, independent, Indigenous-language audiovisual production in Mexico and in Mexican migrant communities in the United States. The contributors relate the styles and forms of collaborative and community media production to socially critical, transformative, resistant, and constitutive processes offscreen, thereby exploring the political within the context of the media."